CHARACTERISTICS AND PREGNANCY OUTCOMES IN WOMEN WITH PREECLAMPSIA: A COMPARISON BETWEEN SPONTANEOUS CONCEPTION AND IN VITRO FERTILIZATION (Vietnam Journal of Community Medicine, 2026)
Objectives: To compare clinical characteristics, disease severity and pregnancy outcomes between spontaneously conceived and in vitro fertilization (IVF) pregnancies among women already diagnosed with preeclampsia.Methods: A retrospective cohort study based on medical-record review was conducted on 607 women with preeclampsia at Hanoi Obstetrics and Gynecology Hospital, 2021–2025 (500 spontaneous, 107 IVF). Clinical, laboratory, and pregnancy outcome data were collected and compared between the two groups. Multivariable logistic and linear regression adjusted for maternal age, parity and multiple pregnancy. Given the substantial difference in the rate of multiple pregnancy between the two groups and the dual role of multiple pregnancy as both a potential confounder and a mediator in the analysis of IVF effects, we additionally performed a repeated analysis restricted to singleton pregnancies.Results: Maternal age, nulliparity and multiple pregnancy were higher in the IVF group (p < 0.05). Rates of severe and early-onset preeclampsia were similar. Platelet count was lower in IVF (p < 0.05) but the proportion with platelets < 100 G/L did not differ (1.9% vs 2.8%, p = 0.75). Pregnancy outcomes were similar between groups. After adjustment, IVF was not independently associated with any outcome.Conclusions: Among women already diagnosed with preeclampsia at the study site, IVF conception was not independently associated with disease severity or pregnancy outcomes after adjustment for maternal age, parity and multiple pregnancy. Further studies stratified by IVF technique are needed for confirmation.
Keywords: preeclampsia, in vitro fertilization, pregnancy outcomes, retrospective cohort.